PENGARUH INDONESIAN DIAGNOSTIC RELATED GROUP (INA-DRG) TERHADAP KELENGKAPAN PENGISIAN RESUME MEDIS PASIEN JAMKESMAS DI RSUD KALIANDA LAMPUNG SELATAN - Yani Haida Shanti; Yati Maryati; Hosizah Hosizah (Indonesian of Health Information Management Journal (INOHIM), 2013)
AbstractThis article discusses about Indonesian influence diagnostic related group (ina-drg) to resume charging completeness medical patients in hospitals Kalianda jamkesmas South Lampung. In the health care system was an enacted JAMKESMAS payment pattern by applying INA-DRG system. Financing system diagnosis related group (DRG) is a system or method of payment by the funders of health care providers (health providers) for convening services, large costs are not calculated based on the type or amount of health services being offered to each patient, but by agreement price according to the diagnosis of diseases in which a group of patients who are being treated are located. INA-DRG (Diagnostic Related Group Indonesian) using the basics in coding using ICD 9 CM to ICD 10 and the action to diagnose the disease, the pattern of the rates specified amount of an average patient stay and long stay patients in accordance with the code of the disease suffered by patients treated so long hospitalization was determined and adjusted to the prevailing rates in the INA-DRG. Medical resumes charging completeness prior to implementation of INA-DRG still shows that there is still low awareness of health practitioners in the medical resume charging completeness. This is because there is no requirement in terms of the completeness of filling the whole medical resume. Completeness of medical resumes charging after INA-DRG implementation has already shown that there are very significant and meaningful changes, but there are certain parts that are still not discovered the change, namely the charging of physical examination items. There INA-DRG influence on the completeness of patient medical resume charging JAMKESNASKeywords: ina-drg, resume medic, implementation